INDUSTRIAL MAINTENANCE: A STUDY OF ITS IMPORTANCE IN COMPETITIVENESS IN A METALLURGICAL BRANCH COMPANY. - Nascimento, João Pedro; Midori Yada de Almeida, Marcela (Revista Interface Tecnológica, 2021)
With industrial competitiveness and the emergence of production and process management techniques and strategies, maintenance stands out. Knowing that it is formed by a set of techniques and operational and administrative activities, its use in a cohesive way as a tool for process improvement and eventually cost reduction is fundamental. In Brazil, companies have a large scale of assets (machines), for the production of goods and services, ensuring the longest useful life of this equipment is crucial. Among the objectives of the project, there is the importance of maintenance to reduce costs, define goals and organizational objectives through the procedures to obtain the best use of time, space, machinery and people. The study was developed through quantitative research on business data and qualitative through bibliographic review on websites, articles and monographs. The results of maintenance as a strategic tool are intertwined with the availability of its equipment, resulting in productivity playing a crucial role for the organization.